Effect of Deposition Temperature and Electrolytic Cell Concentration on Phase Transformation at Nanoscale - Mukhtar, A.; Mehmood, T. (The Nucleus, 2016)
The coexistence of both hcp and fcc phases for Co nanowires was studied in this work. Both hcp and fcc Co nanowires with diameter of ~ 50nm were successfully prepared by adjusting the deposition parameters. The systematic results show the effect of electrolytic cell with different cobalt sulfate concentration and different deposition temperatures with same pH and potential for the formation of (fcc and hcp) Co nanowires. The fabricated nanowires were characterized by X-ray diffraction, and the morphology of the electrodeposited nanowires was explored by scanning electron microscope.